Empirical Analysis of Money Demand Function with Economic Uncertainty - Gan, Pei-Tha; Lim, Siew-Yong; Mohd Hussin, Mohd Yahya bin; Muhammad, Fidlizan bin (International Journal of Economics and Financial Issues, 2015)
The studies on the demand for money rarely focus on the economic uncertainty rather than the scale variable (i.e., output), opportunity cost variables (i.e., interest rate and inflation rate) and external variable (i.e., exchange rate). To overcome this matter, this paper examines the relationships between the demand for money and economic uncertainty in 9 selected countries, including 4 selected developed countries and 5 selected developing countries. The findings suggest that the optimal economic uncertainty index can serve as an uncertainty indicator in signaling central bank’s economic policy decision making. This paper also suggests that the output, interest rate, inflation rate and exchange rate are useful indicators for the central bank’s economic policy decision making. Keywords: Demand for Money; Optimal Economic Uncertainty Index; Uncertainty JEL Classifications: C1; C33; E44